KINERJA PEMERINTAH DAERAH DI MATA PUBLIK: STUDI KASUS PENANGANAN PANDEMI COVID-19 DI BALI TAHUN 2020 - Kadek Dwita Apriani (Journal Publicuho, 2022)
Bali is one of the region in Indonesia experiencing an upmost severe impact of Covid-19 pandemy. Policies formulation and implementation were done in unideal condition. The evaluations from the public opinion are really needed. This study captures the public's response over the policy of pandemic handling in Bali which is focused on the aspects of: (1) health, (2) tourism economy, and (3) social welfare. The method used in this study is survey conducted on 1.540 respondents spread all over Bali. The margin of error is 3% at the confidence level of 95%. The results showed that public values the performance of Bali Government is lower than national scores (66%). Good satisfaction numbers are shown over the health aspect (62%). Balinese rate over economic and public welfare sectors are valued as 42%. This research also found that public's response over Bali Province government policies in pandemic handling are related with the pandemic impact on respondents household financial situations.